An efficient algorithm for solving nonlinear Volterra–Fredholm integral equations - Chen, Zhong; Jiang, Wei (Applied mathematics and computation, 2015)
In this work, we develop a new effective method for solving nonlinear Volterra–Fredholm integral equation. The existence of any ε-approximate solution is proved. At the same time, an effective method for obtaining the ε-approximate solution is established. The final numerical examples illustrate that our approach is valid not only for weakly nonlinear problems but also for strongly nonlinear problems.